An Empirical Investigation of Changing Trend Patterns of Foreign Direct Investment (FDI) in India - Gupta, Honey; Jaiswal, Krishna Kumar (Indian Journal of Finance, 2017)
The globalization and liberalization of the economy gave an opportunity to the foreign entities to invest their surplus funds in other countries. In the recent past, India has witnessed a substantial rise in the foreign direct investment inflows and with this, India emerged as one of the most preferred destinations for foreign direct investment in the world in 2015. Although the foreign direct investment has been increasing, but the period after 2008 witnessed fluctuations and diminishing growth. Hence, the present study attempted to empirically analyze the trends and patterns of yearly inflow of foreign direct investment in the country (2001 - 2016) and forecasted the inflows of foreign direct investment in India in the next 5 years and also appraised the progress of flow of FDI in terms of entry route - wise, investing country - wise, and sector - wise (2006 - 2016). It is apparent from the study that though foreign direct investment showed an increasing trend, but its growth rate over previous years fluctuated vigorously. The trend analysis revealed that there will be an increasing trend of foreign direct investment inflows in India in the future. There has been a rise in the share of Singapore, Japan, and U.S.A in the total foreign direct investment in India during the past decade, while the share of Mauritius and UK in the total foreign direct investment in India declined. Among the top five sectors, the contribution of the service sector and the construction development sector in the total foreign direct investment declined, while the contribution of the automobile industry increased considerably.